Hepcidin is a friend rather than a foe in COVID19-induced complications.: Hepcidin preserves COVID-19 complications - Sukhomlin, Tatiana (Acta Biomedica Atenei Parmensis, 2020)
Clinical observations in concert with literary data demonstrate that detrimental complications of COVID19-induced pathology (acute respiratory distress syndrome, multi-organ failure, Kawasaki-like disease etc.), could result from a disturbance of local iron homeostasis (FeH) in damaged tissues followed by abnormal coagulation in small vessels. To resolve these complications the local FeH needs to be recovered. Hepcidin, as a master regulator of FeH is both a major player in the recovery and a marker of an efficacy of the restoration. Therefore, both local and systemic hepcidin levels could serve as a dynamic marker of disease progression (the more hepcidin the worse is disease) and treatment efficacy (after iron homeostasis is recovered hepcidin disappears). On the contrast, artificial attempts to suppress hepcidin expression directly or application of hepcidin antagonists could be detrimental. Overall, more comprehensive research of hepcidin role in COVID-19 pathology is needed.